Organization and planning of marketing service activities at a production enterprise - pcadmin, Baymukhamedova Gulnoza Fattakhovna (Academia One Publishing, 2025)
Organization and planning of marketing service activities at a production enterprise is one of the important processes. The Marketing service is engaged in the development and implementation of strategies aimed at bringing the enterprise's products to the market, establishing contact with consumers and increasing their competitiveness. This article will tell you in detail about the processes of organization and planning of the activities of the marketing service at the production enterprise, their significance and basic principles.
Keywords: development enterprises